A Simulation Framework For Performance Evaluation Of Network Selection Algorithms In Heterogeneous Wireless Networks. - Hasib, Abdul; O. Fapojuwo, Abraham (2010)
Future wireless communication systems will be comprised by the integration of different radio access technologies (RATs), referred to as heterogeneous wireless network (HWN).